Shift Toward Randomness in Brain Networks of Patients With Anorexia Nervosa: The Role of Malnutrition - Collantoni, Enrico; Meneguzzo, Paolo; Tenconi, Elena; Meregalli, Valentina; Manara, Renzo; Favaro, Angela (Frontiers in Neuroscience, 2021)
Previous research found reduced white matter (WM) integrity in anorexia nervosa (AN), but no study to date investigated structural connectome characteristics in these patients. Our study aims at exploring the characteristics of the WM network architecture in AN. 36 patients with AN and 36 healthy women underwent magnetic resonance imaging to obtain a high-resolution 3D T1-weighted anatomical image and a Diffusion Tensor Imaging scan. Probabilistic tractography data were extracted and analyzed in their network properties through graph theory tools. In comparison to healthy women, patients with AN showed lower global network segregation (normalized clustering: p=0.029), an imbalance between global network integration and segregation (i.e., lower small-worldness: p=0.031), and the loss of some of the most integrative and influential hubs. Both clustering and small-worldness negatively correlated with the severity of body mass index. A significant relationship exists between the average regional loss of cortical volume and changes in network properties of brain nodes: the more the difference in the cortical volume of brain areas, the more the increase in the centrality of corresponding nodes in the whole brain, and the decrease in clustering and efficiency of the nodes of parietal cortex. Our findings showed an unbalanced connectome wiring in AN patients, which seems to be influenced by malnutrition and loss of cortical volume. The role of this rearrangement in the maintenance and prognosis of anorexia nervosa and its reversibility with clinical improvement need to be established by future studies.